2007
DOI: 10.1080/14748460701241444
|View full text |Cite
|
Sign up to set email alerts
|

Making physical education relevant: increasing the impact of initial teacher training

Abstract: This paper is developed from concern that, despite a number of developments and initiatives in physical education over recent years, there has been little change in the teaching of the subject. This has resulted in many young people being alienated from physical education and therefore physical activity. The paper focuses on how initial teacher training (ITT) contributes to this lack of change by focusing on the development of knowledge for teaching and the technical competence to deliver this. It then cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 91 publications
2
37
0
1
Order By: Relevance
“…This is seen to limit early teacher's in their exploration of the more problematic nature of teaching PE (Capel and Blair, 2007;Eames et al, 2011) and gives limited recognition to 'why aspects are being taught, focusing more on the 'what' and 'how'' (Williams, 2012, p. 47). Furthermore, Kelly, Hickey and Tinning (2000, p. 293) contend that developing PE pedagogy has 'no choice but to recognise the uncertain nature of truth-telling that characterises processes of reflexive modernization'.…”
Section: Towards An Acceptance Of Uncertainty and Contingencymentioning
confidence: 99%
See 3 more Smart Citations
“…This is seen to limit early teacher's in their exploration of the more problematic nature of teaching PE (Capel and Blair, 2007;Eames et al, 2011) and gives limited recognition to 'why aspects are being taught, focusing more on the 'what' and 'how'' (Williams, 2012, p. 47). Furthermore, Kelly, Hickey and Tinning (2000, p. 293) contend that developing PE pedagogy has 'no choice but to recognise the uncertain nature of truth-telling that characterises processes of reflexive modernization'.…”
Section: Towards An Acceptance Of Uncertainty and Contingencymentioning
confidence: 99%
“…Secondary features which emerged from the programme encouraged trainees to problematise their own practice, to focus not only on the what and how of practice but also on the why, and, to systematically develop skills of critical and reflective practice. These are elements of practice that have been argued as lacking in both teacher training (Capel and Blair, 2007) and, teacher professional development (Chappell, 2014;.…”
Section: The Risk-taking Professional Development Programmementioning
confidence: 99%
See 2 more Smart Citations
“…A concern is that student teachers and their school mentors often have limited understanding and ability to implement teaching skills to create an effective learning environment (pedagogical knowledge) (Tindall and Enright, 2013). Moreover, it has been suggested that many (student) teachers' have only a basic content knowledge of the different activities or sports (Capel and Blair, 2007;Siedentop, 2002). As a result, student teachers often focus largely on the acquisition of sport techniques (Capel, 2007).…”
Section: Factors Influencing Teachers' Interpretation and Delivery Ofmentioning
confidence: 99%